2015
DOI: 10.1093/mnras/stv2290
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a brown dwarf companion to the A3V star β Circini

Abstract: We report the discovery of an L dwarf companion to the A3V star β Circini. VVV J151721.49-585131.5, or β Cir B, was identified in a proper motion and parallax catalogue of the Vista Variables in the Vía Láctea survey as having near infrared luminosity and colour indicative of an early L dwarf, and a proper motion and parallax consistent with that of β Cir. The projected separation of ∼3.6 ′ corresponds to 6656 au, which is unusually wide. The most recent published estimate of the age of the primary combined wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…in Zurlo et al (2016), we smoothed these spectra to the IRDIS resolution using the IRDIS passbands, a model of the Paranal atmospheric transmission using the ESO Skycalc web applica- 5 (Noll et al 2012;Jones et al 2013) and a model spectrum of Vega (Bohlin 2007). We also show the positions of substellar companions with an age comparable to that of HR 2562 B (Luhman et al 2007;Goldman et al 2010;Wahhaj et al 2011;Bowler et al 2013;Naud et al 2014;Gauza et al 2015;Smith et al 2015;Bowler et al 2017) as stellar age is known to be a relevant parameter for the spectral and photometric characterization of substellar objects. HR 2562 B sits at the L-T transition, very near to the location of (although slightly redder than) HN Peg B that has comparable age (300-400 Myr) and mass (∼20M Jup ), according to Luhman et al (2007).…”
Section: Color-magnitude Diagrammentioning
confidence: 81%
“…in Zurlo et al (2016), we smoothed these spectra to the IRDIS resolution using the IRDIS passbands, a model of the Paranal atmospheric transmission using the ESO Skycalc web applica- 5 (Noll et al 2012;Jones et al 2013) and a model spectrum of Vega (Bohlin 2007). We also show the positions of substellar companions with an age comparable to that of HR 2562 B (Luhman et al 2007;Goldman et al 2010;Wahhaj et al 2011;Bowler et al 2013;Naud et al 2014;Gauza et al 2015;Smith et al 2015;Bowler et al 2017) as stellar age is known to be a relevant parameter for the spectral and photometric characterization of substellar objects. HR 2562 B sits at the L-T transition, very near to the location of (although slightly redder than) HN Peg B that has comparable age (300-400 Myr) and mass (∼20M Jup ), according to Luhman et al (2007).…”
Section: Color-magnitude Diagrammentioning
confidence: 81%
“…A search of SIMBAD and the literature indicates that three of these systems are known: TYC 7365-318-1 AB was identified by Kurtev et al (2017), and L 149-77 AB and L 200-41 AB were identified by Ivanov et al (2013). Note that the β Circini system identified by Smith et al (2015) does not appear in this list since β Circini does not appear in TGAS. The remaining 25 common proper motion pairs were previously unidentified.…”
Section: Tgas Common Proper Motion Companionsmentioning
confidence: 99%
“…The dispersion along the line is 33 mas yr −1 . We also compared our results with those generated in the PhD thesis of Leigh Smith (Smith 2015) (see Fig.1, lower inset). In this case the dispersion is only 7 mas yr −1 which is an expected result because the study is based on the VVV data too.…”
Section: The Pm Cataloguementioning
confidence: 94%
“…The total number of the previously known PM stars is less than a sum of the stars in each catalogue because some of the stars are presented in more than one catalogue. Discovery of a brown dwarf companion to the A3V star β Circini Smith et al (2015) In total, 348 known PM object from all 3003 stars in our list (∼11.5%).…”
Section: The Pm Cataloguementioning
confidence: 99%
See 1 more Smart Citation